Exercise as a therapeutic strategy for depression in menopausal women: a metaanalysis of randomized trials - Li, Sen; Dou, Yan; Li, Ye (Frontiers in Psychiatry, 2025)
BackgroundMenopause is a transitional phase in a woman’s life marked by a heightened vulnerability to depressive symptoms. Exercise has emerged as a promising non-pharmacological strategy for alleviating depression, yet the extent to which different intervention characteristics influence outcomes remains unclear.ObjectiveThis meta-analysis aimed to evaluate the overall effectiveness of exercise interventions in reducing depressive symptoms among menopausal women and to examine potential moderators through detailed subgroup analyses.MethodsA comprehensive search of four databases identified 16 randomised controlled trials (RCTs) meeting the inclusion criteria. Standardised mean differences (SMDs) were calculated to quantify effect sizes. Subgroup analyses were conducted based on exercise format (individual vs. group), exercise type, session length, total intervention duration, and menopausal stage. Sensitivity analysis and Egger’s test were used to assess result stability and publication bias, respectively.ResultsExercise interventions were associated with a significant reduction in depressive symptoms (SMD=–1.04, 95% CI: –1.46 to –0.63, p < 0.00001). Subgroup analyses indicated that individual-based formats, mind-body exercises (e.g., yoga, tai chi), longer sessions (60–90 min), extended intervention durations (>12 weeks), and interventions during the perimenopausal stage produced greater effects. Egger’s test suggested no significant publication bias (p=0.441), and sensitivity analyses confirmed the robustness of the findings.ConclusionExercise is an effective intervention for reducing depressive symptoms in menopausal women. The magnitude of benefit varies by intervention characteristics, underscoring the need for personalised, phase-specific exercise prescriptions. These findings provide a strong evidence base for integrating structured exercise into mental health strategies targeting midlife women.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251046026.